"The right thing to do?" Transformation in South African sport. Issue 3 (1st September 2017) - Penrose, Brian
Abstract : In this paper I attempt to unpack the current public debate on racial transformation in South African sport, particularly with regard to the demographic make-up of its national cricket and rugby sides. I ask whether the alleged moral imperative to undertake such transformation is, in fact, a moral imperative at all. I discuss five possible such imperatives: (1) the need to compensate non-white South Africans for the injustices in sport's racist history, (2) the imperative to return the make-up of our national sides to what they would have been in the absence of that history, (3) the requirement that national sides be representative of the country, (4) the need to eliminate ongoing racial bias in selection, and (5) the obligation to provide all South Africans, regardless of their race, the opportunity to compete as equals for places in the national side. I argue that the first three, drawn from talk of "rectifying the injustices of the past", "achieving demographic proportionality between the sides and the country", "representivity", and "transformation" itself, are not compelling. The remaining two are of great moral import, but, I argue, they have little to do with the sorts of phrases just mentioned, and which are frequently used in the debate.